Cognitive factors can influence self-motion perception (vection) in virtual reality - Riecke, Bernhard E.; Schulte-Pelkum, Jörg; Avraamides, Marios N; Heyde, Markus Von Der; Bülthoff, Heinrich H (ACM Transactions on Applied Perception (TAP), 2006)
Research on self-motion perception and simulation has traditionally focused on the contribution of physical stimulus properties (“bottom-up factors”) using abstract stimuli. Here, we demonstrate that cognitive (“top-down”) mechanisms like ecological relevance and presence evoked by a virtual environment can also enhance visually induced self-motion illusions (vection). In two experiments, naive observers were asked to rate presence and the onset, intensity, and convincingness of circular vection induced by different rotating visual stimuli presented on a curved projection screen (FOV: 54° × 45°). Globally consistent stimuli depicting a natural 3D scene proved more effective in inducing vection and presence than inconsistent (scrambled) or unnatural (upside-down) stimuli with similar physical stimulus properties. Correlation analyses suggest a direct relationship between spatial presence and vection. We propose that the coherent pictorial depth cues and the spatial reference frame evoked by the naturalistic environment increased the believability of the visual stimulus, such that it was more easily accepted as a stable “scene” with respect to which visual motion is more likely to be judged as self-motion than object motion. This work extends our understanding of mechanisms underlying self-motion perception and might thus help to improve the effectiveness and believability of virtual reality applications.
Keywords: Measurement; Psychophysics; Riecke; Riecke_2006; Vection; bernhard-riecke; ego--motion simulation; experimentation; human factors; human information processing; iSpaceWeb; journalPaper; markus-von-der-heyde; spatial orientation; spatial presence; vection; virtual reality